Effect of soil texture, moisture regimes and cultivars on root and shoot development in upland rice (Oryza sativa) - SINGH, R K; SINGH, C V; SINHA, P K; SINGH, V P; MAITI, D; PRASAD, K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted on root and shoot systems during 1994 and 1995 on 6 upland fice (Oryza sativa L.) cultivars (Japonica, Indica, Aus and Zero groups) grown in PVC pipes filled with sandy and sandy loam soils under stressed (booting to harvest stage) and watered conditions. The component of root and shoot systems included, tiller number, shoot dry weight, shoot height and diameter, adventitious root number, root diameter, rooting depth, root weight, root mass distribution in soil layers. The result showed that the tiller number, shoot weight, shoot height and shoot diameter decreased due to stress but drought resistant Japonica cultivars had higher tiller number and drought susceptible Indica rices had higher shoot due to stress in sandy soil. The reduction in shoot weight due to stress in Japonica rice grown in sandy soil was less (5.3%), whereas the reduction was higher (10.1-24.2%) in Indica rice. The tiller nuruber had direct relationship with adventitious root number and root number had inverse relationship with root diameter. The magnitude of total root weight and root: shoot ratio differed within the rice cultivars and the root weight and root: shoot ratio was higher due to stress in all cultivars. The Japonica rices gave higher root weight than Indica, Aus and Zero group rices. The root diameters were affected due to stress as well as due to soil type. The root diameter decreased due to stress in sandy loam soil and increased in sandy soil. Under watered condition the root concentration was more in surface layer and under stress, the roots moved downwards in deeper layer.